2016
DOI: 10.3151/jact.14.108
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Confined Boundary Regions of RC Walls under Cyclic Reversal Loadings

Abstract: Observed damages in reinforced concrete wall buildings following some recent earthquakes raised concerns about the seismic performance of rectangular RC walls. Damages in RC walls included spalling and crushing of concrete and longitudinal reinforcement buckling at boundaries as well as global buckling. Preliminary studies attributed these damages to the lack of adequate confinement and detailing in wall boundary regions and high axial load level. Prism specimens representing wall boundaries were tested to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This has become a popular form of experimental testing in recent years (e.g. [13][14][15][16][17][18]) and is commonly referred to as 'prism testing'. This form of testing allows for the performance of various RC wall end region detailing techniques to be experimentally assessed for different failure mechanisms (e.g.…”
Section: Testing Methodology and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…This has become a popular form of experimental testing in recent years (e.g. [13][14][15][16][17][18]) and is commonly referred to as 'prism testing'. This form of testing allows for the performance of various RC wall end region detailing techniques to be experimentally assessed for different failure mechanisms (e.g.…”
Section: Testing Methodology and Backgroundmentioning
confidence: 99%
“…The prism testing performed in literature currently includes: 9 specimens tested by Patel et al [13], which were small specimens with one central bar; 1 specimen tested by Segura et al [14], which was a ductile prism specimen with a small height-to-thickness ratio of 6.0; 16 specimens tested by Taleb et al [15], which were all ductile prism specimens with small to moderate height-to-thickness ratios of 5.4 to 8.8; 33 specimens tested by Welt et al [16], which included both non-ductile and ductile prism specimens with small to moderate height-to-thickness ratios of 4.0 to 8.9, however only 1 non-ductile specimen was tested under cyclic actions with the others under monotonic loading; 8 specimens test by Hilson [17], which were all non-ductile prism specimens with a small height-to-thickness ratio of 5.0; and 12 specimens tested by Rosso et al [18], which were non-ductile specimens with central reinforcement and very slender height-to-thickness ratios of 24 to 30. The studies by Hilson [17] and Rosso et al [18] represent the best test programs identified in literature for non-ductile boundary elements.…”
Section: Testing Methodology and Backgroundmentioning
confidence: 99%
“…Appendix B: Application to calculate embedded reinforcing steel bar buckling compression envelope and length Taleb et al [Taleb, Tani and Kono (2016) Parameters for Steel4 material model (compression model) -Kin apply kinematic hardening $bk: 0.001 (hardening ratio) 0 $ R b : 8.0, $r1: 0.91, $r2: 0.15 -iso apply isotropic hardening $bi: -0.048 (initial hardening ratio) $bl: 0.0000002 (saturated hardening ratio) $rhoi: -0.83 (specifies the position of the intersection point between initial and saturated hardening asymptotes) $Ri: 2.0 (control the exponential transition from initial to saturated asymptote) $Iyp: 0.0 (length of the yield plateau) -ult apply an ultimate strength limit $fu: 347 (MPa) (ultimate strength) $ Ru: 5.0 (control the exponential transition from kinematic hardening to perfectly plastic asymptote)…”
Section: Resultsmentioning
confidence: 99%
“…The modeling for buckling length of reinforcing steel bars embedded in RC elements developed above is validated using experimental test results of RC members presented in Taleb et al [Taleb, Tani and Kono (2016)] and Welt et al [Welt, Massone, Lafave et al (2017)]. In total, five specimens representing boundary elements of RC walls with different levels of confinement tested under monotonic compression load are used to validate the use of the analytical buckling length model in assigning parameters to the reinforcing steel uniaxial material model used in fiber-section modeling of RC members under compression.…”
Section: R =mentioning
confidence: 99%
“…A research program was undertaken in order to study the effects of end regions confinement on the seismic performance of moderate aspect ratio type of structural walls [11,12]. Four 40%-scale RC walls having different cross sectional configurations and transverse reinforcement at their confined end regions of were constructed and tested under lateral cyclic reversed loading.…”
Section: Introductionmentioning
confidence: 99%